Patient Perception of Tics - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The subjective perception of abnormal movements was determined in 170 patients with various hyperkinesias at the Movement Disorders Clinic, Toronto Western Hospital, Toronto, Ontario.